ADDRESSING THE ABILITIES OF LANGUAGE LEARNERS (Ustozlar uchun, 2025)
article examines the abilities of language learners and highlights the importance of considering individual differences in language learning. It discusses cognitive, linguistic, affective, and social abilities and explores strategies for addressing diverse learner needs in the classroom. Practical recommendations for educators to enhance learning outcomes and promote effective language acquisition are provided.